The Differential Impacts of Hard and Soft Infrastructure on Rural Poverty: Evidence from Karanganyar Regency - David Andrean; Sarjiyanto; Malik Cahyadin (Universitas Tidar, 2026)
Local infrastructure development is often promoted as a key strategy to reduce rural poverty, however, micro-level empirical evidence in Indonesia remains relatively limited, particularly at the village level. This paper examines whether hard (physical) and soft (social-economic) infrastructure have different impacts on rural poverty, an important issue given policymakers’ tendency to prioritize physical infrastructure development. The novelty of this study lies in explicitly separating infrastructure into hard and soft categories and comparing their heterogeneous effects on poverty reduction, thereby addressing a gap in previous studies that tend to treat infrastructure as a single and homogeneous indicator. Using cross-sectional data from the 2018 PODES covering 177 villages in Karanganyar Regency, this study applies an Ordinary Least Squares (OLS) estimation approach to analyze the relationship between infrastructure availability and rural poverty, proxied by the number of poor households. The findings show that soft infrastructure: digital access, financial inclusion, public spaces, agricultural services, and health facilities has significant negative effect on rural poverty, whereas hard infrastructure such as electricity, mobility, and trade facilities has no significant effect. The study concludes that soft infrastructure plays a more decisive role in reducing rural poverty, highlighting the need for policies that prioritize social–economic support systems alongside physical development.